Enhancement of Reverse Intersystem Crossing in Charge‐Transfer Molecule through Internal Heavy Atom Effect. (3rd August 2021) - Kim, Hyung Suk; Lee, Ja Yeon; Shin, Seongjun; Jeong, Wonkyo; Lee, Sang Hoon; Kim, Seonghyeon; Lee, Jihoon; Suh, Min Chul; Yoo, Seunghyup
Abstract: Thermally activated delayed fluorescence (TADF) is beneficial for improving the efficiency of organic light‐emitting diodes (OLEDs) by providing pathways to convert non‐emissive triplet excitons into singlet excitons. To ensure TADF is efficient, it is critical to enhance the reverse intersystem crossing (RISC) rate. To this end, most approaches propose thus far have focused on reducing the energy difference between S1 and T1 states. The present study explores how incorporating the internal heavy atom (IHA) effect can impact the RISC and device performance. By introducing a series of halogen atoms to charge‐transfer molecules, TADF molecules exhibiting RISC over 7 × 10 7 s −1 are realized. These molecules are then applied to OLEDs, and the effect of incorporating these moieties is investigated. The results show that efficiency roll‐off is still significant even with RISC‐enhanced TADF emitters. Spectroscopic and theoretical results indicate that a fast RISC may not be the sole factor important for reducing efficiency roll‐off and that the spin‐flip cycles considering both T1 →S1 and S1 →T1 should be carefully taken into account to derive a complete picture of the IHA effect on efficiency roll‐off behavior. Abstract : This study explores how incorporating the internal heavy atom (IHA) effect can impact the reverse intersystem crossing (RISC) and device performance. The spectroscopic and theoretical results indicate that a fast RISC may not be the sole factor important for reducing efficiency roll‐off and that the spin‐flip cycles should be carefully considered to derive a complete picture of the IHA effect.